Metagenomics and its Application in Rumen Ecosystem: Potential Biotechnological Prospects - Ghazanfar, Shakira; Azim, Atiya (Pakistan Journal of Nutrition, 2009)
Genetic and biological diversity of microorganisms is an important area of scientific research. Considering the importance of ruminants in livestock strategies their ability to converts locally available feedstuff to animal products should be improved. Recent advances in the molecular biology and genomics now offer new opportunities to conduct a more holistic examination of the structure and function of rumen communities. To understand the complex microbial communities function and how microbes interact within their niches represents a major challenge for rumen microbiologists today. Metagenomics has the potential for providing insight into the functional dimensions of the rumen genomic database and will help to achieve a major goal of rumen microbiology; the complexities of microbial communities function and interaction among these microbes. This review summarizes the molecular methods of culture-independent insight 'metagenomics' and their recent application to studies of the rumen ecosystem for enhancing the livestock productivity.